Retinal vasculitis - Shrestha, JK; Khadka, D; Lamichhane, G; Khanal, S (Nepalese Journal of Ophthalmology, 2010)
Retinal vasculitis is an idiopathic inflammatory venous occlusion primarily affecting the peripheral retina of otherwise healthy young adults. Eales' disease is recognized as primary vasculitis of unknown etiology occurring in young adults. This article aims at the overall review of the etiopathogenesis, clinical presentations, pathology, management and prognosis of retinal vasculitis. Key words: Retinal vasculitis; Eales' disease DOI: 10.3126/nepjoph.v1i1.3675 Nep J Oph 2009;1(1):66-71